To determine the zeros of the quadratic function \( y = -x^2 + 16x - 39 \), we can use the quadratic formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
Here, \( a = -1 \), \( b = 16 \), and \( c = -39 \).
First, we calculate the discriminant \( b^2 - 4ac \):
\[ b^2 = 16^2 = 256 \] \[ 4ac = 4 \cdot (-1) \cdot (-39) = 156 \] \[ b^2 - 4ac = 256 - 156 = 100 \]
Now substituting the values into the quadratic formula:
\[ x = \frac{-16 \pm \sqrt{100}}{2 \cdot -1} \]
Calculating the square root and the formula:
\[ \sqrt{100} = 10 \] \[ x = \frac{-16 \pm 10}{-2} \]
This gives us two solutions:
- For \( x = \frac{-16 + 10}{-2} \):
\[ x = \frac{-6}{-2} = 3 \]
- For \( x = \frac{-16 - 10}{-2} \):
\[ x = \frac{-26}{-2} = 13 \]
Therefore the zeros of the quadratic function are \( x = 3 \) and \( x = 13 \).
To summarize:
- Smaller zero: \( x = 3 \)
- Greater zero: \( x = 13 \)
Final answer:
smaller zero: \( x = 3 \); greater zero: \( x = 13 \)